Adsorption kinetics of 20 glucocorticoids at environmentally relevant concentrations in wastewater by powdered activated carbons and development of surrogate models. (December 2022) - Zhang, Ai; Luo, Yuxin; Jia, Ai; Park, Minkyu; Daniels, Kevin D.; Nie, Xuhao; Wu, Shimin; Snyder, Shane A.
Abstract: Glucocorticoids (GCs) are widely used in the treatment of the coronavirus disease of 2019 (COVID-19), and the toxicity of GCs to aquatic organisms has aroused widespread concern. Powdered activated carbon (PAC) has proven effective in removing various trace organic pollutants. In this study, the adsorption behaviors of 20 typical GCs onto PACs were investigated at environmentally relevant concentrations (ng/L) in real wastewater, using four commercially available PACs (HDB, WPH, 20BF, PWA). The results showed that PAC adsorption was feasible for GC removal at ng/L concentrations. After adsorption for 60 min, the GC removal efficiencies obtained by HDB, WPH, 20BF, and PWA were 90–98 %, 89–97 %, 84–96 %, and 71–90 %, respectively. The adsorption processes of 20 GCs on PACs were well fitted by the pseudo-second-order kinetics model (with R 2 >0.98). Among the four PACs, HDB achieved the highest rates because of the electrostatic attraction between HDB (positively charged) and the complex of GCs and natural organic matter (GC-NOM, negatively charged). Among the 20 GCs, compounds with substitutions of halogen atoms or five-membered rings at C-17 achieved higher adsorption rates because of the enhanced formation of hydrogen bonds and a resulting increase in electron density. In addition, surrogate models with total fluorescence (TF) and ultraviolet absorbance at 254 nm (UV254 ) were developed to monitor the attenuation trend of GCs during adsorption processes. Compared with the UV254 model, the TF model showed better sensitivity to GC monitoring, which could greatly simplify the water quality monitoring process and facilitate online monitoring of GCs in water. Graphical abstract: Unlabelled Image Highlights: Powdered activated carbon can remove glucocorticoids (GCs) rapidly in water. The adsorption efficiency orders were HDB > 20BF > WPH > PWA. The positively charged surface of HDB enhanced the adsorption diffusion. The substitution at the C-17 of GCs enhanced the adsorption interaction. The TF and UV254 surrogate models are useful for GC attenuation prediction.